A passive filtering solution for overvoltage mitigation in doubly fed induction generator–based wind system fed by long power cable. Issue 3 (June 2021) - Krim, Ali; Lakrim, Abderrazak; Tahri, Driss
The inclusion of the latest generation of semiconductor switches in today's wind farms allows high-frequency pulse width modulation. When the cable that connects the power inverter to the rotor of a doubly fed induction generator is long, the impedance mismatch between it and the rotor leads to overvoltage spikes at the terminals of this last. Such high voltage would cause the deterioration of the rotor winding or the cable insolation. For this reason, it is mandatory to solve this problem. Active and passive filters are considered as classical solutions for this issue. In this context, this article proposes an "RL" filter dedicated to suppress this overvoltage spikes. The design methodology and system modeling are presented in detail. To show the effectiveness of our proposal, a simulation is performed under ANSYS Simplorer. An accurate time-domain model of the cable is used to check the robustness of the filter. The obtained results validate the proposed filtering solution.